Structural Model of Fundamental Decisions of Parental Involvement and Its Types Based on The Gender (Male and Female) of Elementary School Students - Nezamparast , Mahbobe; Talepasand, Siavash; Moradi, Shahab (Journal of Assessment and Research in Applied Counseling (JARAC), 2023)
Objective:  The current research aimed to construct a structural model of the fundamental decisions of parental involvement and its forms based on the gender (male and female) of elementary school students.Materials and Methods:  The design of this research was correlational, employing modeling methods. The study population consisted of all elementary school students in Tehran for the academic year 2020-21. The sample included 386 parents of these students, selected through random cluster sampling. The data collection tools in this research included 6 scales present in the Hoover-Dempsey and Sandler (2005) model of parental involvement. The data of this research were analyzed using SPSS23 and SMART PLS software, employing structural equation modeling as the statistical analysis method.Findings:  The findings of the research showed that the latent construct of forms of parental involvement has a direct structural effect on the latent construct of school-based behaviors. The latent construct of forms of parental involvement also has a direct structural effect on the latent construct of home-based behaviors. The latent construct of forms of parental involvement with the latent construct of school-based behaviors is significantly moderated by gender. The latent construct of forms of parental involvement with the latent construct of home-based behaviors is also significantly moderated by gender, meaning that gender plays a moderating role between the variables, and parental involvement of sons at home is more than that of daughters.Conclusion: The study concludes that parental involvement in children's education is significantly influenced by the gender of the child, with sons experiencing more involvement at home compared to daughters. Both home-based and school-based parental behaviors are directly affected by the forms of parental involvement, highlighting the critical role of gender as a moderating factor in these educational dynamics.